Realization of Zakat as A Form of Social Justice in the Perspective of Muhammad Iqbal - Reni Waningsih; Rokhmat Subagiyo; M. Aqim Adlan (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
The problem that occurs in the distribution of zakat is poverty data, which can hinder the process of zakat distribution, causing individuals who are not eligible to receive zakat to feel a lack of social justice. Social justice in Islam, especially through the concept of zakat, is a crucial focus for Muhammad Iqbal. Zakat is not just a ritual obligation but also an instrument to reduce social injustice and strengthen societal solidarity. Iqbal sees it as a practical step to create a more just and balanced society, viewing zakat as a moral and social foundation. This writing aims to explore the realization of zakat as a manifestation of social justice from the perspective of Muhammad Iqbal. The research approach used in this study is qualitative, employing a literature review method to gather data from various sources such as books such as the book “Introduction to Islamic Economics and History of Islamic Economics”, and International journals, sinta 2 and sinta 5, which are relevant to the research as well as other sources that can support the research. The method used in this research involves the analysis of several articles. The results of the research indicate that, according to Muhammad Iqbal, zakat is not only a religious obligation but also a tangible tool for creating a more humane society with social justice.